(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Colorectal cancer is the third most frequently diagnosed cancer in both genders and the fourth foremost cause in respect to cancer-associated mortality. The metastasis mechanism of colorectal cancer shows that it gradually developed in the form of polyps under granular cells in the large intestine, which damages blood and lymph vessels. At present, chemotherapy and surgery are the major clinical approaches in treatment. Therefore, developing novel and effective drugs are requiring use of natural derivative compounds, a potent and significant effect in restricting the progression of colorectal cancer (CRC). The present research investigates the in vitro anticancer properties of various extracts of plant Oxalis corniculata counter cell viability of CRC cell line (HCT116) using an MTT assay. In silico docking studies of hexadecanoic acid were performed with cytochrome P450CYP17A1 protein (3RUK) to predict potential inhibitors and druglikeness as potential CRC inhibitors using ADME profiling adhered to five rule of Lipinski. The finding indicated the extracts of the Oxalis corniculata have anticancer and anti-proliferative activity. The cell cytotoxic observed against chloroform extract exhibited the highest inhibition against the HCT116 cell line, following ethanol and aqueous extract. The determined IC50 values for the ethanol, aqueous, and chloroform extracts were 53.94±1.29 µg/ml, 61.85±0.43 µg/ml, and 47.34±1.24 µg/ml, respectively The in silico molecular docking result shows that n-hexadecanoic acid compound was found to be effective against 3RUK protein associated with CRC. Therefore, the finding suggests Oxalis corniculata plants could be used to formulate potential therapeutic drugs for the development of anticancer agents.